Navigating vaccination in pregnancy: Qualitative study in 21 ethnically diverse pregnant women - Mohammad S. Razai; Michael Ussher; Lucy Goldsmith; Sally Hargreaves; Pippa Oakeshott (PLoS ONE, 2025)
Background Vaccination during pregnancy is crucial for safeguarding maternal and neonatal health, but vaccination rates remain suboptimal, especially in women from Black and Asian ethnic minorities. We explored the perspectives and decision-making processes of pregnant women regarding uptake of the three recommended vaccines in pregnancy: Influenza, Pertussis (whooping cough) and COVID-19. We also explored women’s attitudes to taking part in vaccine trials during pregnancy and the use of artificial intelligence (AI) to obtain information on vaccines. Methods In 2023, we conducted in-depth telephone interviews with ethnically diverse pregnant women in the Greater London area using convenience and snowball sampling. The interviews focused on participants’ views on vaccination during pregnancy, participation in vaccine trials, information-seeking behaviours, and attitudes to emerging technologies for health information. Interviews were transcribed verbatim and thematically analysed. The data collection and analysis were conducted alongside the iterative development of the topic guide and coding framework, with key themes emerging through collaborative team discussions. Results Twenty one pregnant women aged 20–39 were interviewed of whom 67% were from ethnic minorities and 29% were from migrant backgrounds. Half the participants (53%) reported hesitancy towards at least one of the vaccines. The analysis revealed several themes: concerns about vaccine safety, particularly regarding newer vaccines due to lack of long-term data; reliance on healthcare professionals for guidance, balanced with personal research; and a strong desire for clear and comprehensive information specifically tailored to pregnant women. Pregnant women reported insufficient information, explanation, or recommendation by midwives. Additionally, there was widespread refusal regarding participation in vaccine trials; and mixed responses to the use of AI (such as chatbots) for obtaining vaccine information. Conclusions Pregnant women’s vaccination decisions are complex and require clear, unambiguous communication from healthcare providers, especially midwives, to address their specific concerns. Although information obtained via AI can be useful, responses were mixed.